2019
DOI: 10.31857/s0869-78092019248-55
|View full text |Cite
|
Sign up to set email alerts
|

The background content of heavy metals in the water of small rivers in the Nadym – Pur interfluvial area

Abstract: This article considers the problem of the formation of the microelement water composition of the small rivers not directly affected by the oil and gas industrial complex in the Nadym-Pur interstream area. Physicochemical characteristics and ionic composition of the natural water samples are determined by chemical aqueous method, the total content of heavy metals is analyzed by inductively coupled plasma atomic emission spectrometry (ICP-AES) and inductively coupled plasma mass spectrometry (ICP-MS). More than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Besides, the transparency of water depends on its color, and the water color in 2020 varied on average from 42.8° to 127.3° (the average for the entire period is 69.2°) (Figure 3), and in all sampling periods did not meet the hygienic standards (no more than 30), the excess was up to 42.7-324.3 %. The water color is mainly due to the presence of humus substances and trivalent iron compounds [6] and can be the first sign of a dangerous situation -deteriorates the physical properties of water, leads to extraneous odors, harms the development of aquatic plant and animal organ-isms as a result of a sharp decrease in the concentration of dissolved oxygen in water, which is used to oxidize iron compounds and humus substances [7]. Medium reaction (pH) affects the transformation processes of various forms of nutrients, changes the toxicity of pollutants, affects the chemical processes and activities of aquatic plants and animals, decomposition processes of dying organisms, solubility of minerals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the transparency of water depends on its color, and the water color in 2020 varied on average from 42.8° to 127.3° (the average for the entire period is 69.2°) (Figure 3), and in all sampling periods did not meet the hygienic standards (no more than 30), the excess was up to 42.7-324.3 %. The water color is mainly due to the presence of humus substances and trivalent iron compounds [6] and can be the first sign of a dangerous situation -deteriorates the physical properties of water, leads to extraneous odors, harms the development of aquatic plant and animal organ-isms as a result of a sharp decrease in the concentration of dissolved oxygen in water, which is used to oxidize iron compounds and humus substances [7]. Medium reaction (pH) affects the transformation processes of various forms of nutrients, changes the toxicity of pollutants, affects the chemical processes and activities of aquatic plants and animals, decomposition processes of dying organisms, solubility of minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Medium reaction (pH) affects the transformation processes of various forms of nutrients, changes the toxicity of pollutants, affects the chemical processes and activities of aquatic plants and animals, decomposition processes of dying organisms, solubility of minerals. The pH range is vital for biological objects since each species can only live in a specific pH range; for example, for carp, the pH limits are 4.5-10.8 [6]. It was found that the lake water pH is on average 8.68 (8.4 to 9.0), refers to slightly alkaline and alkaline waters, and the saturation of the lake water with dissolved oxygen was 7.84-8.45 mg/dm 3 ( With a range from 571.0 mg/dm 3 to 987.0 mg/dm 3 , the average content of sulfates was 696.22 mg/dm 3 (Table 2), i.e., there is an excess of the maximum allowable concentration (MAC) standards by 5.7-9.9 times, which contributes to the deterioration of the organoleptic water properties.…”
Section: Resultsmentioning
confidence: 99%
“…This water is used for drinking by Indigenous residents. The methods for determining the elemental composition of the lake and snowmelt waters are described in our previous studies [19,39] and in the online Supplementary Material File S1. The maximum volume of liquid water is located between the surface and 0.5 m deep (Table 1), and the remainder of the column is frozen to the bottom.…”
Section: Geochemistry Of Potential Drinking Water From Natural Source...mentioning
confidence: 99%
“…Snow in the Arctic region has very low concentrations of Mg, K, and Ca; thus, the available water resources are poor in minerals [38,39]. This low mineral concentration in potable water is insufficient for replenishing and maintaining the micronutrient balance in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Источником соединений железа и марганца являются болотные воды, питающие малые реки и ручьи бассейна р. Северная Двина. Соединения меди и цинка попадают в природные воды в результате процессов разрушения и растворения горных пород и минералов, а наличие части органических соединений обусловлено процессами разложения растительных остатков [8]. Однако эпизодические превышения ПДК нефтепродуктов уже обусловлены антропогенным воздействием.…”
Section: водопотреблениеunclassified